Topographical patterns of whole-brain structural alterations in association with genetic risk, cerebrospinal fluid, positron emission tomography biomarkers of Alzheimerâs disease, and neuropsychological measures - Dayor Piersson, Albert; Mohamad, Mazlyfarina; Rajab, Nor Fadilah; Suppiah, Subapriya (Springer, 2021)
This study aimed at investigating the topographical pattern of whole-brain structural alterations in association with apolipoprotein E e4 (APOE e4), cerebrospinal fluid (CSF) [amyloid-beta 42 (Aβ42), and neurofibrillary tau protein], positron emission tomography (PET) biomarkers [Aβ, tau, and 2-[18F]fluoro-2-deoxy-d-glucose (FDG)], and neuropsychological measures. PubMed, Scopus, Ovid, and Cochrane databases were searched. Risk of bias (using a modified Newcastle–Ottawa Scale) and level of evidence were determined. One hundred and thirty-one studies met the inclusion criteria. APOE e4 effect is exerted on the whole-brain. Still, the medial temporal lobe is the most affected, with moderate evidence observed across the lifespan (except late mid-life) and in the AD continuum. Moderate to strong evidence shows that atrophy of AD-vulnerable regions is associated with reduced CSF Aβ42, increased Aβ- and tau-PET, and increased CSF tau. No association between gray matter changes and FDG-PET measures in healthy late mid-life and older adults. Preliminary findings demonstrate a relationship between hippocampal atrophy and lower episodic memory in early life. Moderate evidence of an association between hippocampal atrophy and lower episodic memory is observed in late mid-life. In contrast, hippocampal atrophy is associated with reduced episodic memory and global cognition in older APOE e4 carriers. Strong evidence suggests that atrophy of the AD vulnerable regions is associated with CSF and PET biomarkers and cognitive measures. These relationships may be potentially helpful in characterizing the preclinical and clinical stages of MCI and AD and predicting AD progression.